LITERASI DAN PELATIHAN MANAGEMENT CLOUD COMPUTING BAGI GURU-GURU DALAM MENYIMPAN DATA SEKOLAH BERBASIS DIGITAL DI SMK NEGERI 5 MUARO JAMBI: Pelatihan Penyimapan Google Drive - Willy Riyadi; Ibnu Sani Wijaya ISW; Jasmir; Pareza Alam Jusia; Amroni; Khairuldi (LPPM Universitas Dinamika Bangsa, 2023)
In the current world of information technology, digital data is very important and efficient for all activities carried out by us in the work we do, including teaching staff such as teachers, lecturers and others. Many free platforms are provided by several companies that provide online storage (cloud computing) such as Google Drive, Dropbox, One Drive, and others. However, based on interviews with the school principal and observations made at SMK Negeri 5 Muaro Jambi, they have not utilized this online storage. Whereas those in teacher activities when reporting data such as grades and others must be submitted digitally and also stored in online storage. But the teachers at the school have not been able to apply these rules because they do not have the ability or expertise to operate digital data that is stored online (cloud computing). From these problems, teachers at SMK Negeri 5 Muaro Jambi need to improve their ability to process digital-based data stored online, in this case using Google Drive. The activity planning was carried out in the SMK Negeri 5 Muaro Jambi laboratory with the participants being teachers at the school. The output target of this activity is the publication of a journal in the Community Service Journal, Dinamika Bangsa University Jambi.